Prevalence of syphilis, HIV and toxoplasmosis in prenatal screening in the population of the northern region of the state of Rio de Janeiro, Brazil - Almeida, Yasmim Henrique de Souza; Fernandes, Hugo Freitas Viégas; Rosas, Carolina Maria Leal; Menezes, Ellen Diniz de; Fernandes, Regina Célia de Souza Campos; Souza, Thais Louvain de (Brazilian Journal of Sexually Transmitted Diseases, 2021)
Introduction: There is a need for studies to know the real situation and outline measures to guarantee a reduction in the rates of pregnant women diagnosed with HIV, Syphilis and Toxoplasmosis. Objective: To determine the prevalence of Syphilis, HIV and toxoplasmosis in puerperal women assisted at the largest public maternity hospital in Campos dos Goytacazes in 2016. Methods: Cross-sectional study, using secondary data from the puerperal women assisted at the largest maternity hospital in the northern region of the State of Rio de Janeiro, in the year 2016. Results: There were 970 puerperal women, with a prevalence of HIV, Syphilis and Toxoplasmosis in pregnancy of 1.6, 2.7 and 2%, respectively. Most pregnant women were diagnosed at delivery due to low serological coverage during pregnancy. Conclusion: The high prevalence of Syphilis, HIV and Toxoplasmosis in pregnancy requires efficient prenatal care for its identification and approach.